Drónok a horizonton, gyerekjáték vagy új veszélyes üzem? - Szikora, Veronika; Szilágyi, Gábor (Debreceni Jogi Műhely, 2017)
The reason why We have chosen this topic for my research is that new technologies have appeared in our environment, particularly the unnamed aerial vehicle. In Hungary, similarly to some other countries, there is a gap in the legislation concerning the use of UAV. The UAV technology raises many questions because these vehicles can be used for several reasons. It is necessary to analyse in depth the legal environment of UAV and to change our perspective because it is not enough to consider the legal context; technical and other aspects have to be taken into consideration as well. Most academic sources concerning the usage of UAV focus on the military use of UAV. In my research I focus on the topic from the aspects of civil law; the reason for this is that I consider the legal restrictions concerning the ordinary vehicles used for everyday purposes not for governmental ones. The main goal of our paper is to study how the usage of UAV can be legally controlled. This question is important because the number of these vehicles are gradually growing which leads to several legal issues, for instance privacy or tort. In our research We have analyzed the international laws and regulation plans, the international laws, draft legislation. The „abnormally dangerous activities” that appear in the title of the paper is only a call for attention to evaluate the liability in the civil law. The other aim of our paper is to make a proposal to set up a work group who is going to work out the regulations in detail. Legislators and researchers could participate in the work group, among whom are technical and legal professionals as well.